Understanding “scaleup” location choices in European cities: an empirical analysis - Pérez-Benítez, Virginia; Gemar, Pablo; Gemar, German (Revista de Estudios Empresariales. Segunda Época, 2025)
This study investigates the factors influencing scaleup location choices in European cities using a diverse dataset and statistical techniques such as PLS-SEM. According to the literature, a scaleup is a new entrepreneurial company, up to 10 years old, that has achieved a stable and consistent growth rate. The results highlight the significant relationships between scaleup location choices and factors like city climate, working environment, technological development, and educational level. A sequential model shows the direct and positive effect of education on scaleup location choices, while also revealing relationships between city climate, working environment and technology. The research offers valuable insights for policymakers and entrepreneurs seeking to enhance cities’ attractiveness for scaleup businesses. Fostering a supportive entrepreneurial ecosystem, promoting technological development, and improving the working environment emerge as key strategies for attracting and retaining scaleup companies in European cities. This study contributes to the literature on urban entrepreneurship and regional development by exploring the impact of novel variables and examining the role of the entrepreneurial ecosystem.